2023
DOI: 10.1002/advs.202206521
|View full text |Cite
|
Sign up to set email alerts
|

Lymph Node Follicle‐Targeting STING Agonist Nanoshells Enable Single‐Shot M2e Vaccination for Broad and Durable Influenza Protection

Abstract: The highly conserved matrix protein 2 ectodomain (M2e) of influenza viruses presents a compelling vaccine antigen candidate for stemming the pandemic threat of the mutation-prone pathogen, yet the low immunogenicity of the diminutive M2e peptide renders vaccine development challenging. A highly potent M2e nanoshell vaccine that confers broad and durable influenza protectivity under a single vaccination is shown. Prepared via asymmetric ionic stabilization for nanoscopic curvature formation, polymeric nanoshell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 64 publications
(54 reference statements)
0
9
0
Order By: Relevance
“…Importantly, M2ex3 I3-01v9a and BG505 Env I3-01v9 SApNPs showed significantly longer follicular retention than the SARS-CoV-2 spike-presenting I3-01v9 SApNP (∼8 weeks vs ∼2 weeks), , suggesting a correlation between SApNP retention and antigen thermostability (a T m value of 65 °C or greater for M2ex3 and BG505 Env vs 48 °C for SARS-CoV-2 spike). Of note, a shorter follicular retention (<2 weeks) was reported for a recently developed M2e vaccine, in which M2e peptides were encapsulated within a poly­( d,l -lactide- co -glycolide), or PLGA, polymer matrix, possibly due to polymer degradation and/or M2e peptide release. Next, we examined the accumulation and retention patterns of these three M2ex3 immunogens at 2 and 5 weeks using a prime-boost regimen (injected into 4 footpads at weeks 0 and 3, 10 μg/footpad) (Figure G).…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…Importantly, M2ex3 I3-01v9a and BG505 Env I3-01v9 SApNPs showed significantly longer follicular retention than the SARS-CoV-2 spike-presenting I3-01v9 SApNP (∼8 weeks vs ∼2 weeks), , suggesting a correlation between SApNP retention and antigen thermostability (a T m value of 65 °C or greater for M2ex3 and BG505 Env vs 48 °C for SARS-CoV-2 spike). Of note, a shorter follicular retention (<2 weeks) was reported for a recently developed M2e vaccine, in which M2e peptides were encapsulated within a poly­( d,l -lactide- co -glycolide), or PLGA, polymer matrix, possibly due to polymer degradation and/or M2e peptide release. Next, we examined the accumulation and retention patterns of these three M2ex3 immunogens at 2 and 5 weeks using a prime-boost regimen (injected into 4 footpads at weeks 0 and 3, 10 μg/footpad) (Figure G).…”
Section: Resultsmentioning
confidence: 92%
“…In our current study, the trafficking and retention of M2ex3 I3-01v9a SApNP were quantified via immunostaining of tandem M2e antigens displayed on SApNPs using an M2e-specific antibody (mAb148) at individual time points. In comparison, a previous study conjugated fluorescent dyes to the M2e peptide, which may have influenced the experimental readouts due to signal degradation in vivo over time.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Unlike HA and NA, M2e-specific antibodies protect via FcγR-dependent mechanisms, such as antibody-dependent cellular cytotoxicity (ADCC) and phagocytosis (ADCP), rather than direct neutralization ( 39, 4143 ). Various carriers have been used to increase the immunogenicity of M2e vaccines, including hepatitis B core protein (HBc) ( 41 ), tobacco mosaic virus (TMV) coat protein ( 44 ), keyhole limpet hemocyanin (KLH) ( 40 ), rotavirus NSP4 ( 45 ), GCN4 ( 46 ), bacterial flagellin ( 47 ), liposomes ( 48 ), polymers ( 4951 ), and gold nanoparticles (NPs) ( 52, 53 ). Early human trials confirmed the immunogenicity and tolerance of M2e vaccines but also revealed several weaknesses.…”
Section: Introductionmentioning
confidence: 99%